2021
DOI: 10.1002/ajpa.24426
|View full text |Cite
|
Sign up to set email alerts
|

Predicting skeletal stature using ancient DNA

Abstract: Objectives: Ancient DNA provides an opportunity to separate the genetic and environmental bases of complex traits by allowing direct estimation of genetic values in ancient individuals. Here, we test whether genetic scores for height in ancient individuals are predictive of their actual height, as inferred from skeletal remains. We estimate the contributions of genetic and environmental variables to observed phenotypic variation as a first step towards quantifying individual sources of morphological variation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 100 publications
1
26
0
Order By: Relevance
“…These scores have been used to provide a window into the phenotypic diversity of past populations (Mathieson et al, 2015;Berens et al, 2017;Martiniano et al, 2017) and to disentangle genetic and environmental contributors to temporal phenotypic variation (e.g. at the Neolithic transition; Cox et al, 2019Cox et al, , 2021Marciniak et al, 2021). Such studies are most convincing when there are relevant phenotypic measurements on at least some ancient individuals and polygenic prediction accuracies can be judged.…”
Section: Considerations For Applications Of Gwas Results Across Groupsmentioning
confidence: 99%
“…These scores have been used to provide a window into the phenotypic diversity of past populations (Mathieson et al, 2015;Berens et al, 2017;Martiniano et al, 2017) and to disentangle genetic and environmental contributors to temporal phenotypic variation (e.g. at the Neolithic transition; Cox et al, 2019Cox et al, , 2021Marciniak et al, 2021). Such studies are most convincing when there are relevant phenotypic measurements on at least some ancient individuals and polygenic prediction accuracies can be judged.…”
Section: Considerations For Applications Of Gwas Results Across Groupsmentioning
confidence: 99%
“…R. Soc. B 377: 20200416 transition; [109][110][111]). Such studies are most convincing when there are relevant phenotypic measurements on at least some ancient individuals and polygenic prediction accuracies can be judged.…”
Section: (B) Considerations For Applications Of Gwas Results Across G...mentioning
confidence: 99%
“…They concluded that realized height changes are partially predicted by genetics, with both temporal trends having a period of constancy between the Mesolithic and Neolithic, and an increase between the Neolithic and Bronze Age. A follow-up study by Cox et al (2021) used polygenic scores for height to show that PRS predicts 6.8% of the observed variance in femur length in ancient skeletons, after controlling for other variables. This is approximately one quarter of the predictive accuracy of PRS in present-day populations, which the authors attribute to the low-coverage aDNA data used in their study.…”
Section: R a F Tmentioning
confidence: 99%
“…When used to compute polygenic scores for ancient populations, only a subset of GWAS variants can be used, which substantially reduces predictive accuracy. Cox et al (2021) estimate that the combined effect of low-coverage and pseudo-haploid genotypes reduced their predictive accuracy by approximately 75%, when compared…”
Section: -Limitations and Caveats Specific To Ancient Dnamentioning
confidence: 99%
See 1 more Smart Citation